Multiscale textured, ultralight graphene monoliths for enhanced CO2 and SO2 adsorption capacity. (15th June 2016) - Yun, Sol; Lee, Hyunjoo; Lee, Wang-Eun; Park, Ho Seok
Graphical abstract: Highlights: 3D hierarchically porous graphene-based adsorbents were synthesized by self assembly. Surface area and porosity of graphene adsorbents were significantly improved by steam activation. Steam activated graphene adsorbents showed high CO2 and SO2 adsorption capacity. Steam activated graphene adsorbents revealed the fast adsorption kinetics. Abstract: The porous graphene-based materials are regarded as a promising adsorbent for the adsorption of greenhouse gases such as CO2 and SO2 due to their excellent physical and textural properties, but the adsorption capacity needs to be improved by creating multiscale porosity and large surface area. In this study, we present the synthesis of three-dimensional (3D) ultralight, macro- and micro-porous reduced graphene oxide (m 2 -RGO) monoliths through a self-assembly and steam activation process. Along with 3D macrosopic frameworks, the as-obtained adsorbents possess a ultralow density of 10.4 mg/cm 3, a large specific surface area of >1600 m 2 /g and a ultrahigh porosity of >98%, which is suitable for high performance adsorbents. As a consequence of multiscale porosity and good textures, the m 2 -RGO adsorbents exhibit much higher capacities of 6.31 mmol/g and 2.97 mmol/g compared to 2.68 mmol/g and 1.36 mmol/g of 3D macro-porous reduced graphene oxide (m-RGO) for the capture of CO2 and SO2 gases. Moreover, the adsorption kinetics of the m 2 -RGO is much faster than that of commercial RGO powder due to the 3D interconnected macroporous pathways.